Observed magnitude and trends in socioeconomic and geographic area inequalities in obesity prevalence among non-pregnant women in Chad: evidence from three waves of Chad demographic and health surveys - Gebretsadik Shibre; Betregiorgis Zegeye; Gashaw Garedew Woldeamanuiel; Wassie Negash; Gorems Lemma; Mitku Mamo Taderegew (BMC, 2021)
Abstract Background While the prevalence of obesity is increasing worldwide, the growing rates of overweight and obesity in developing countries are disquieting. Obesity is widely recognized as a risk factor for non-communicable diseases (NCDs), including diabetes, cancer and cardiovascular diseases. Available evidence on whether obesity has been more prevalent among higher or lower socioeconomic groups, across regions and urban-rural women's are inconsistent. This study examined magnitude of and trends in socioeconomic, urban-rural and sub-national region inequalities in obesity prevalence among non-pregnant women in Chad. Method Using cross-sectional data from Chad Demographic and Health Surveys (DHSs) conducted in 1996, 2004 and 2014; we used the World Health Organization (WHO) Health Equity Assessment Toolkit (HEAT) to analyze socio-economic, urban-rural and regional inequalities in obesity prevalence among non-pregnant women aged 15-49 years. Inequalities were assessed using four equity stratifiers namely wealth index, educational level, place of residence and subnational region. We presented inequalities using simple and complex as well as relative and absolute summary measures such as Difference (D), Population Attributable Risk (PAR), Population Attributable Fraction (PAF) and Ratio (R). Results Though constant pattern overtime, both wealth-driven and place of residence inequality were observed in all three surveys by Difference measure and in the first and last surveys by Ratio measure. Similarly, including the recent survey (D = -2.80, 95% CI:-4.15, − 1.45, R = 0.37, 95% CI: 0.23, 0.50) absolute (in 1996 & 2014 survey) and relative (in all three surveys) educational status inequality with constant pattern were observed. Substantial absolute (PAR = -2.2, 95% CI: − 3.21, − 1.34) and relative (PAF = − 91.9, 95% CI: − 129.58, − 54.29) regional inequality was observed with increasing and constant pattern by simple (D) and complex (PAR, PAF) measures. Conclusion The study showed socioeconomic and area-based obesity inequalities that disfavored women in higher socioeconomic status and residing in urban areas. Prevention of obesity prevalence should be government and stakeholders' priority through organizing the evidence, health promotion and prevention interventions for at risk population and general population.